Predation on larval Atlantic herring (Clupea harengus) in inshore waters of the Baltic Sea. (5th November 2017) - Kotterba, Paul; Moll, Dorothee; von Nordheim, Lena; Peck, Myron A.; Oesterwind, Daniel; Polte, Patrick
Abstract: In fishery science, early life-stage survival and development are regarded as major factors driving the population dynamics of marine fishes. During the last century, the main research focus has been on the spatio-temporal match of larval fish and appropriate food ( bottom-up processes). However, these field studies are often criticised for their limited capability to disentangle their results from mortality caused by predation since these top-down mechanisms are rarely studied. We examined the predation on herring ( Clupea harengus ) larvae in a Baltic inshore lagoon by investigating the spatio-temporal overlap of larval herring and their potential predators such as the dominant threespine stickleback ( Gasterosteus aculeatus ) in distinct habitats (sublittoral and littoral areas) using a set of different gears and sampling techniques. Despite significant spatial and temporal predator-prey overlap, stomach analyses suggested that very few larvae were consumed by sticklebacks, even if projected to the entire study area and season. Other well-known predators of clupeid larvae such as gelatinous plankton occur later in the year after young herring have migrated out of the system. The observed predation on herring larvae was much less than expected and appears being a minor factor in determining herring reproduction success in our study area, particularly if compared to other causes of mortality such as egg predation. Providing a relatively good shelter from predation might be a key element making transitional waters valuable nursery grounds for the offspring of migrating marine fish species.